Dinamika Politik Hukum Islam Dalam Revisi UU Perkawinan: Menelisik Peran Fatwa MUI dan Kepentingan Negara - Fairusah, Qonita Najmah; Sirojuddin, Ahmad Sholihin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The change in the minimum age of marriage in Law Number 1 Year 1974, which was revised through Law Number 16 Year 2019, has become an important issue in legal and social discourse in Indonesia. This revision equalises the minimum age of marriage between men and women to 19 years. The data analysis method used is descriptive analysis, which describes in detail and in depth to obtain an accurate understanding. In the midst of these changes, the Indonesian Ulema Council (MUI) performs a strategic role as a religious institution that influences the direction of legal policy through fatwas and political lobbying. This study analyses how MUI's fatwa operates in the political context of Islamic law, including its influence on state regulation and its relationship with power and the prevailing patriarchal ideology. Although MUI initially rejected the revision, the institution's position changed following pressure from civil society and a Constitutional Court ruling. This analysis shows that MUI's fatwa serves not only as religious guidance, but also as a tool of social and political legitimacy in the national legislative process, particularly in issues involving religious values and human rights.